Using the Schmahmann Syndrome Scale to Assess Cognitive Impairment in Young Adults with Metabolic Syndrome: A Hypothesis-Generating Report - Kotkowski, Eithan (Cerebellum, 2020)
The posterior cerebellum is the most significantly compromised brain structure in individuals with metabolic syndrome (MetS) (Kotkowski et al., 2019). In light of this, we hypothesized that cognitive decline reported in patients with MetS is likely related to posterior cerebellar atrophy. In this study, we performed a post-hoc analyses using T1-weighted magnetic resonance imaging (MRI), diffusion tensor imaging (DTI) in the form of voxel-wise tract-based spatial statistics (TBSS), biometric, and psychometric data from young participants with (n = 52, aged 18–35 years) and without MetS (n = 52, aged 18–35 years). To test the predictive value of components of the Schmahmann Syndrome scale (SSS), also known as the cerebellar cognitive affective syndrome scale, we used structural equation modeling to adapt available psychometric scores in our participant sample to the SSS and compare them to the composite score of all psychometric data available. Our key findings point to a statistically significant correlation between TBSS fractional anisotropy (FA) values from DTI and adapted SSS psychometric scores in individuals with MetS (r(2) = .139, 95% CI = 0.009, .345). This suggests that the SSS could be applied to assess cognitive and likely neuroanatomical effects associated with MetS. We strongly suggest that future work aimed at investigating the neurocognitive effects of MetS and related comorbidities (i.e. dyslipidemia, diabetes, obesity) would benefit from implementing and further exploring the validity of the SSS scale in this patient population.